Endoparasites of horses from the Formiga city, located in center-west region of the state of Minas Gerais, Brazil - Pires Teixeira, Weslen Fabricio [UNESP]; Felippelli, Gustavo [UNESP]; Cruz, Breno Cayeiro [UNESP]; Maciel, Willian Giquelin [UNESP]; Favero, Flavia Carolina [UNESP]; Costa Gomes, Lucas Vinicius [UNESP]; Buzzulini, Carolina [UNESP]; Prando, Luciana [UNESP]; Bichuette, Murilo Abud [UNESP]; Zanetti Lopes, Welber Daniel [UNESP]; Oliveira, Gilson Pereira de [UNESP]; Costa, Alvimar Jose da [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
With the aim of studying the endoparasite fauna of horses from the Formiga city, located in center-west region of the state of Minas Gerais, 25 animals that were naturally infected with helminths were evaluated. By means of parasitological necropsies, different endoparasites were found. The subfamily Cyathostominae presented the highest incidence, followed by Trichostrongylus axei, Oxyuris equi, Triodontophorus serratus, Strongyloides westeri, Strongylus edentatus, Habronema muscae, Parascaris equorum, Probstmayria vivipara, Strongylus vulgaris, Gasterophilus nasalis, Anoplocephala magna and Anoplocephala perfoliata. In the present study, if the species Probstmayria vivipara was not considered in the prevalence, the frequency of Cyathostominae was equivalent to 94.85%. The results obtained in this study allowed us to detect and identify different species of helminths in horses, and confirmed the high incidence of nematodes belonging to the subfamily Cyathostominae in the center-west region of Minas Gerais.

Com o objetivo de estudar a fauna de endoparasitas de equinos da Região Centro-Oeste do Estado de Minas Gerais, 25 animais naturalmente infectados por helmintos foram avaliados. Por meio de necropsias parasitológicas, diferentes endoparasitas foram identificados. A sub - família Cyathostominae apresentou maior incidência, seguido por Trichostrongylus axei, Oxyuris equi, Triodontophorus serratus, Strongyloides westeri, Strongylus edentatus,Habronema muscae, Parascaris equorum, Probstmayria vivipara, Strongylus vulgaris, Gasterophilus nasalis,Anoplocephala magnae Anoplocephala perfoliata. No presente estudo, se não for considerada a espécieProbstmayria vivipara na prevalência, a frequência de Cyathostominae é equivalente a 94,85%. Os resultados obtidos neste estudo, permitiu detectar e identificar diferentes espécies de helmintos em equinos, bem como confirmar a elevada incidência de nematódeos pertencentes à sub-família Cyathostominae na Região Centro-Oeste de Minas Gerais.
Keywords: Endoparasites; helminth; horse; parasite; Helmintos; equinos; parasitas